2020
DOI: 10.3390/cancers12040934
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic Risk Detection in Patients with Polycythemia Vera: The Predictive Role of DNMT3A/TET2/ASXL1 Mutations

Abstract: The development of thrombotic events is common among patients with polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF). We studied the influence of pathogenic mutations frequently associated with myeloid malignancies on thrombotic events using next-generation sequencing (NGS) in an initial cohort of 68 patients with myeloproliferative neoplasms (MPN). As expected, the presence of mutations in DNMT3A, TET2, and ASXL1 (DTA genes) was positively associated with age for the whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…Genetic analyses have led to the description of diverse non-driver mutations in patients with PV, particularly as a result of NGS studies. These include SNVs in genes that encode proteins that regulate epigenetic processes, such as TET2, DNMT3A, ASXL1, EZH2 , and IDH1/2 , as well as proteins implicated in the splicing of messenger RNA, such as SRSF2, SF3B1 and U2AF1 [ 12 , 106 ], with non-driver mutations detected by NGS in 53% and 75% of PV patients according to two recent studies [ 107 , 108 ].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic analyses have led to the description of diverse non-driver mutations in patients with PV, particularly as a result of NGS studies. These include SNVs in genes that encode proteins that regulate epigenetic processes, such as TET2, DNMT3A, ASXL1, EZH2 , and IDH1/2 , as well as proteins implicated in the splicing of messenger RNA, such as SRSF2, SF3B1 and U2AF1 [ 12 , 106 ], with non-driver mutations detected by NGS in 53% and 75% of PV patients according to two recent studies [ 107 , 108 ].…”
Section: Diagnosismentioning
confidence: 99%
“…TET2 SNVs are particularly common in PV, detected in between approximately 10% and 36% of patients [ 12 , 106 , 108 , 120 , 121 ], and are frequent in both JAK2 V617F-positive and -negative MPN. Experiments in mice suggested that mutated TET2 confers a clonal advantage to cells mutated in JAK2 that accelerates their proliferation [ 122 , 123 ].…”
Section: Diagnosismentioning
confidence: 99%
“…ASXL1 mutations include frameshift mutations, nonsense mutations, and missense mutations, of which frameshift are the most frequently happened mutations [19]. Studies have displayed that ASXL1 mutations have been found in patients with a variety of hematological malignancies, including MPN, myelodysplastic syndrome (MDS), acute myeloid leukemia (AML), and chronic myelomonocytic leukemia (CMML) [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In the NGS study by Tefferi et al, they showed an association between TET2 mutations and thrombosis in patients with ET independently of both age and driver mutation [59]. Interestingly, Segura-Diaz performed a targeted case-control study of 55 age-matched patients with PV and provided evidence for mutations in TET2 and higher risk of cardiovascular disease and thrombotic events [185]. However, in two other NGS studies, no influence of TET2 mutations on OS in patients with MF [64] or disease progression in ET or PV was observed [86].…”
Section: Tet2 Mutations and Order Of Mutationsmentioning
confidence: 99%